Transcutaneous injection of triamcinolone acetonide for persistent glottic granulation after laser microsurgery - Ying Zhang; Shisheng Li (Brazilian Journal of Otorhinolaryngology, 2023)
Objective: The aim of study was to demonstrate that transcutaneous intralesional injection of Triamcinolone Acetonide (TA) under fibrolaryngoscopy could be an option for persistent granulation after Transoral Laser Microsurgery (TLM) in glottic cancer patients. Methods: We recruited 32 patients, who had conservative treatment but failed. 20 patients accepted TA injection monthly until the granulation disappeared or did not shrink further. 12 patients chose to closely monitor. Results: For the 20 patients, 17 (85.0%) patients’ granulations completely disappeared. 3 (15.0%) patients’ granulations had reduced 80%. For the 12 patients, 3 (25.0%) patients’ granulations disappeared but 9 (75%) patients’ granulations did not have an obvious change. Recurrence was not observed. Conclusion: Our experience showed that transcutaneous intralesional TA injection for persistent granulation after TLM through cricothyroid membrane is an efficient, security, harmless and low recurrence method. Especially suitable for huge granulation which blocks the glottis and recur after a second operation.